Formation of thick spin-on glass (SOG) sacrificial layer for capacitive accelerometer encapsulation - Hamzah, A.A. (2017)
This paper presents a method to form thick spin-on glass (SOG) sacrificial layer for accelerometer encapsulation fabrication. Siloxane type SOG is applied on blank wafers and accelerometer patterns by multiple spin, bake, and cure processes. A series of gradual hot plate baking up to 250°C are experimented for each spun layer. After multiple spin and bake, the SOG layers are etched back in hydrofluoric acid (HF) solution of various concentrations to form rectangular encapsulation bases. 25 samples are prepared for SOG thickness uniformity characterization. Thickness measurements are taken for each sample using thin-film mapper. Surface profiler measurements are subsequently taken using Tencor surface profiler. Scanning electron microscope (SEM) is used to observe surface and etch wall profile after HF etching. No surface cracking was visible under SEM observation. Shallow trench patterns are apparent on SOG deposited on accelerometer pattern. The average sample thickness is 5 urn with 3.7% thickness variation across samples. The average variation within each sample is 0.14 μm with an average of 2.6% thickness variation within sample. These thickness variations are acceptable for encapsulation structure deposition.